A pivotal role of AMPK signaling in medicarpin‐mediated formation of brown and beige. (24th October 2017) - Imran, Khan Mohammad; Yoon, Dahyeon; Kim, Yong‐Sik
Abstract: Obesity poses a substantial threat of a worldwide epidemic and requires better understanding of adipose‐tissue biology as well as necessitates research into the etiology and therapeutic interventions. In this study, Medicarpin (Med), a natural pterocarpan, was selected (by screening) as a small‐molecule inducer of adipocyte differentiation among 854 candidates by using C3H10T1/2 mesenchymal stem cell; a cellular model of adipogenesis. Med induced the expression of brown‐adipocyte commitment marker Bmp7 as well as the early regulators of brown fat fate Pparγ, Prdm16, and Pgc‐1α during differentiation of C3H10T1/2 mesenchymal stem cells. Med also induced the expression of a key thermogenic marker—uncoupling protein 1 (UCP1)—along with expression of other brown‐fat–specific markers and beige‐fat–specific markers. Of note, Med significantly reduced the expression of white fat markers too. Furthermore, Med treatment promoted formation of multilocular lipid droplets (LDs), expression of mitochondrial‐biogenesis–related genes, and increased oxygen consumption. Gene silencing study revealed that Med promotes the development of brown‐ and beige‐adipocyte characteristics in C3H10T1/2 mesenchymal stem cells through activation of the AMPK pathway, and our data allow us to propose Med as a candidate for therapeutics against obesity or related metabolic disorders. © 2017 BioFactors, 44(2):168–179, 2018